Review and perspectives of the strategic partnership China European Union - Higueras, Georgina (Sinología hispánica. China Studies Review, 2024)
The author proposes a commitment to dialogue and good relationships. In summary, she says that the world needs a Europe of peace, dialogue and negotiation, so as not to be the scene of hostilities and in this way, to become an actor to fully participate in the birth of the more just and inclusive multipolar world, which China seeks. Therefore, the author suggests that it is a time for cooperation and not for hegemonic powers, for collaboration and not for conflicts. The comprehensive strategic partnership has been extremely economically beneficial for both China and the European Union. As great defenders of peace and security through dialogue and diplomacy, China and the EU have many possibilities for cooperation: China needs Europe, as Europe needs China. Beijing and Brussels defend their commitment to multilateralism, written in the DNA of the Union, and adopted by China as a tool to continue advancing its development, but their different visions on the role and direction that international institutions should take limit a much-needed cooperation in global governance. They have a complicated journey to trust, cooperation, mutual benefit and equity, but they are moved by different values and rhythms. Therefore, the author suggests that the future of bilateral relations and their comprehensive strategic partnership depends on the two parties learning to dialogue from new realities and committing to building trust and respecting each other.